Effect of Seed Size and Embryo Size on Early Seedling Vigour in Wheat - PRAVEEN K YADAV; MONIKA A JOSHI; DHARMPAL (Seed Research, 2026)
Rapid seedling establishment is an important requirement for successful crop production in dry land farming systems. Seed size, as a characteristic of seed quality, influences seedling growth and establishment. Early vigour has been widely reported to provide improved productivity of wheat in semi-arid environments, and particularly those environments in which rainfall patterns are erratic and crop is to be sown in residual moisture. Hence, in these situations embryo size is an essential parameter which strongly affects seed vigour of crops along with seed size. In lieu of this, the present study was conducted on sixty wheat genotypes, including certain advance wheat lines and released varieties, to study the effect of seed size and embryo size on early seedling vigour. Based on the coleoptile length, the material was categorised into short (2.5-4.5 cm), medium (4.6-6.5 cm) and long (6.6-9 cm) coleoptile length genotypes. These three coleoptile class genotypes had an average 1000- seed weight of 40.24g 43.04g and 43.78g, respectively and an embryo size of 2.261 mm2, 2.3895 mm2 and 2.8395 mm2, respectively. No correlation was observed between 1000 seed weight and different coleoptile length genotype classes, seed vigour index I and II, and seedling emergence percent and hence was found less effective for selection of genotypes for early seedling vigour. Embryo size of more than 3 mm2 was found in majority of long coleoptile genotype group. Higher embryo size was also in correlation with the higher SVI I, SVI II, seedling emergence and shoot length. Therefore embryo size can be utilised as more reliable indicator of higher seedling vigour in early stage of wheat; for development of varieties suitable for dryland agriculture.